CCR5 directs the mobilization of CD11b+Gr1+Ly6Clow polymorphonuclear myeloid cells from the bone marrow to the blood to support tumor development - Hawila, Elias; Blattner, Carolin; Umansky, Viktor (Cell reports, 2017)
Summary: Cells of hematopoietic origin can be subdivided into cells of the lymphoid lineage and those of the myeloid lineage, among which are myeloid-derived suppressor cells (MDSCs). The MDSCs can be further divided into CD11b+Ly6G−Ly6Chi monocytic (Mo) MDSCs and CD11b+Ly6G+Ly6Clow polymorphonuclear (PMN) MDSCs. Both subtypes support tumor growth and suppress anti-tumor immunity. Their accumulation at the tumor site includes mobilization from the bone marrow to the blood followed by colonization at the tumor site. The present study examines the mechanism by which PMN-MDSCs are mobilized from the BM to the blood to later accumulate at the tumor site. We show that the chemokine receptor CCR5 is a key driver of this event. We also show that, beyond chemoattraction, the interaction between CCR5 and its ligands promotes the proliferation of CCR5+ PMN-MDSCs at the BM and, later, potentiates their immune-suppressive activities at the tumor site in part by inducing arginase-1.